A7 THE POLYP-BASED RESECT-AND-DISCARD STRATEGY. (15th March 2019) - Duong, A; Bouin, M; Leduc, R; Deslandres, E; Deshêtres, A; Weber, A; Pohl, H; Barkun, A N; von Renteln, D
Abstract: Background: Current clinical practice assigns post-polypectomy surveillance intervals based on the number, size and histological aspects of polyps. Aims: Our goal was to test a novel polyp-based resect and discard model that assigns surveillance intervals for small polyps based only on size and number of polyps. Methods: A post hoc analysis was performed on patients enrolled in a prospective colonoscopy trial. We created a model for polyp-based surveillance interval allocation based on clinical experience for what the most likely pathology-based surveillance interval would be for certain scenarios. The primary outcome was the surveillance interval agreement of the polyp-based resect and discard strategy compared to histopathology and USMSTF based surveillance intervals. Secondary outcomes were the overall reduction in required pathology exams and the number of surveillance intervals that can be provided immediately to patients before leaving the endoscopy unit. In addition, we conducted a medical chart review to assess current clinical practise of surveillance interval guideline adherence at our institution. Results: 457 patients (mean age 62.7, 49.4% female, 514 small polyps, 430 diminutive polyps) were enrolled in the study. When using the polyp-based resect and discard model, the assigned surveillance intervals were correct for 89, 3% (95% CI: 0.86–92) of patients when compared to pathology-based surveillance interval assignment. When using the polyp-based model, 88, 8% of patients can be provided with immediate surveillance interval recommendations compared to 47, 7% when using the pathology-based surveillance interval allocation. When using the polyp-based model, 61.4% of pathology examinations can be omitted. Medical chart review showed that at our institution 43.8% of patients received a correct surveillance interval recommendation. Conclusions: The polyp-based resect and discard model reaches an almost 90% agreement compared to pathology-based surveillance interval allocation recommendations. This alternative model reduces the need for pathology examinations, increases the amount of patients that can be provided with immediate surveillance interval recommendations and has the potential to reduce colonoscopy-associated costs. Clinical adherence to pathology results and guideline recommendations was found to be low, but in the range of what has been previously reported in the literature. Funding Agencies: None